The Implementation of E-Government through the Use of the Website SIM DARAT (Information System for Distribution and Archiving of Letters) in Archiving Incoming and Outgoing Letters at the Administrative Subdivision of UPT P2TK, Department of Manpower and Transmigration of East Java. - Alvania, Bellinda (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
E-Government is the process of enhancing government operations based on digital technology to improve the quality of public services in a more optimal and timely manner. Technological advancements have had a significant impact on the management of administrative correspondence in various organizations. Methods that were previously manual have now transitioned to more modern (online) approaches. With these technological advancements, time can be saved, work processes simplified, and paper usage reduced. The management of administrative correspondence is a crucial component of government administration that supports smooth communication between agencies, employees, and the public. Additionally, well-organized document archiving is essential to ensure accountability, facilitate document retrieval, and support transparency and effective governance. This study aims to examine the impact of the implementation of the SIM DARAT website (Information System for Distribution and Archiving of Letters) in archiving incoming and outgoing letters at the Administrative Subdivision (Subbag TU) of UPT P2TK Disnakertrans Prov. East Java. The research findings indicate that the use of SIM DARAT enhances archiving efficiency, simplifies access to information, and reduces paper usage.